Manusia Sebagai Subyek Hukum - Gilang Rizki Aji Putra (ADALAH, 2022)
Humans are considered as parties who can act legally. Therefore he is considered a legal subject who has legal authority that is not owned by other parties. There are two categories of legal subjects, namely humans and legal entities. Humans as legal subjects are a nature. The question is, who are the human beings who can become legal subjects? This cannot be answered with just one sentence. Human essence becomes one of the basis to answer it. The next question, what is meant by a legal entity so that it can be domiciled as a legal entity? These are the questions that this paper will answer.